Morphine and opioid peptides reduce inhibitory synaptic potentials in hippocampal pyramidal cells in vitro without alteration of membrane potential. - Siggins, G R (1981)
We used intracellular recording in the hippocampal slice in vitro to characterize further the mechanisms behind the unusual excitatory action of opiates and opioid peptides on hippocampal pyramidal cells in vivo. No significant effect on resting membrane potential, input resistance, or action potential size in cortical area 1 (CA1) pyramidal cells was observed with morphine sulfate, beta-endorphin, [Met5]enkephalin, or [D-Ala2, D-Leu5]enkephalin at 1-50 microM. However, in all cells studied, these agents markedly reduced the size of inhibitory postsynaptic potentials generated by stimulation of the stratum radiatum or alveus. Excitatory postsynaptic potentials were also diminished in many of these cells. The effects of the opioids were antagonized by naloxone. These results are consistent with excitation of pyramidal neurons by a disinhibitory mechanism.